Enhancing epoxy coatings with spherical ZnO nanoparticles for improved hydrophobicity and corrosion resistance - Albarqouni, Yasin M.Y.; Banius, Euodia; Nurul Huda, Abu Bakar; Arman, Abdullah (Taylor & Francis, 2025)
This study explores the integration of spherical zinc oxide (ZnO) nanoparticles into epoxy (EP) coatings to enhance hydrophobicity and corrosion resistance. Through sol-gel synthesis, ZnO nanoparticles with a spherical morphology were successfully fabricated, as confirmed by UV-Vis spectroscopy, FT-IR, XRD, and SEM/EDX analyses. The spherical shape of ZnO facilitated dense packing within the epoxy matrix, significantly improving coating compactness and superhydrophobicity, evidenced by a contact angle of 101.5°, a 17.5% increase over pure epoxy. Electrochemical assessments revealed remarkable corrosion protection: the epoxy-ZnO (EPZ) coating reduced the corrosion rate to 0.00092 mm.y−1 after 5 days of immersion in 3.5% NaCl, outperforming pure epoxy (0.019 mm.y−1). Polarization resistance surged to 2.19 × 106 Ω·cm2, 25 times higher than epoxy alone, while coating resistance reached 3.62 × 105 Ω·cm2, demonstrating superior barrier properties. EDX analysis further highlighted ZnO’s protective role, showing a 46.74% reduction in Al2O3 corrosion products compared to unmodified epoxy. These findings underscore the potential of spherical ZnO nanoparticles to revolutionize protective coatings by combining enhanced hydrophobicity with robust electrochemical stability.